Covid-19 Massive Vaccination Center Layouts: A modular and Scalable Model for Lombardy Region, Italy - Brambilla, Andrea; Mangili, Silvia; Macchi, Marco; Trucco, Paolo; Perego, Alessandro; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: The rapid evolution of Covid-19 and the availability of numerous vaccines led countries to set up Massive Vaccination campaign in a very short time. Since December 2020, due to the lack of specific guidelines, multidisciplinary groups started to investigate the minimum requirements for Massive Vaccination Centers (MVC). The aim of the paper is to shed light on the process of development of a scalable model for MVC layout design and implementation.Methods: The methodology included two phases and six steps: 1)Study of MVC with i) acquisition of process data from experimental study on an early set up vaccination hub; ii) review of scientific literature on MVC; iii) review of existing available guidelines and international examples; 2) Design proposal with iv) functional and space requirements collection; v) standard MVC layout design and vi) scalable model definition.Results: The resulting layout is compact, has a good wayfinding and address safety reducing cross-contamination risks. Different vaccine lines have been designed with a central dilution area for process efficiency. Healthcare staff wellbeing is guaranteed by the provision of resting spaces, short distances, and the correct sizing of space for the different activities. To ensure optimal vaccination capacity at the peak of vaccination, a modular and scalable model of different sizes has been designed ranging from 400 to 12000 m2.Conclusions: The modular layout has been used as basic model in the regional legislation, disclosed with the Deliberation n° XI / 4353 of 24/02/2021. Further research is encouraged to compare different national and international layouts.